Public Digital Infrastructure Investment and Corporate Digital Transformation: Evidence from New Infrastructure Special Bonds in China - Jianxiang Zhang; Maoguang Wang; Xinzi Xia (The Singapore Economic Review, 2026)
Digital transformation has become a critical source of corporate competitiveness, yet the role of public digital infrastructure investment in facilitating this process remains underexplored. This study examines whether new infrastructure special bonds promote corporate digital transformation in China. Using a sample of A-share listed firms from 2010 to 2023, we exploit the staggered issuance of new infrastructure special bonds across cities as a quasi-natural experiment and employ a staggered difference-in-differences model for identification. The baseline results indicate that new infrastructure special bonds significantly enhance corporate digital transformation. This effect intensifies with larger bond issuance volumes, revealing a clear dose-response pattern. Mechanism analysis shows that the policy operates through two channels: improving urban resource allocation efficiency and strengthening digital infrastructure. Heterogeneity tests further demonstrate that the effect is more pronounced in cities with stronger digital governance capacity and among firms in technology-intensive industries. Additionally, Spatial Durbin model estimates reveal significant positive spillover effects on firms located in neighboring cities. This study contributes to the literature on corporate digital transformation by highlighting the enabling role of public finance in shaping firm-level digital behavior.